Work life balance and service delivery among women entrepreneurs in South-Western Nigeria - Mutiat Oyinlola Kuranga (Financial Internet Quarterly, 2020)
Businesses in the twenty first century are characterized by persistent changes, uncertainties and undue pressure to meet demands and increase productivity. For women entrepreneurs, they are expected to combine this with the statutory responsibility of taking care of their children, families and home front. Managing these different roles and responsibilities usually influences the business performance and family life and may impact their service delivery. Hence, the study examined the impact of work-life balance on service delivery among women entrepreneurs in south-western Nigeria. A total of 379 respondents were selected from a population of 25,122 members of the Nigeria union of tailors in Lagos, Oyo and Osun state using multistage sampling techniques. Primary data was collected through the use of a structured self-administered questionnaire and a structural equation model (SEM- PLS) was adopted for the analysis. The result shows work demands, wellbeing, family workload and spousal support with coefficients 0.219, 0.101, 0.061 and 0.563. The study also found that every unit change of work-life balance would lead to a 0.792 unit change in service delivery. Therefore, the study concludes that work-life balance contributes significantly to the service delivery of women entrepreneurs. The study recommends that women entrepreneurs should effectively manage their work and family roles, ensure creativity and flexibility in their work domains and seek support to enable them to deliver efficient service and achieve overall performance in their business.
Keywords: O1; J1; 330; work-life balance; service delivery; women entrepreneurs; performance